Fabrication characteristics and mechanical behavior of Rice Husk Ash-Silicon Carbide reinforced Al-6061 alloy matrix hybrid composite. (2018) - Sarkar, Siddhartha; Bhirangi, Aniket; Mathew, Joel; Oyyaravelu, R.; P.Kuppan,; Balan, A.S.S.
Abstract: From an engineering standpoint, materials have always been preferred which offer high strength at a low cost. This study focuses on the fabrication characteristics and mechanical behaviour of a particular alloy of Aluminium, which is the Al-6061 alloy, reinforced with Silicon Carbide and Rice husk ash, an agro waste derivative. This was aimed at assessing the viability of developing high performance Al matrix composites at a reduced cost. The ratios of RHA and SiC in the composite were 1:4, 2:3 and 0:1 with a weight percentage of 8%. The composites were prepared using the Stir casting method. The density and the percent porosity were determined. SEM and EDX were utilised to get proper microstructure images as well as Tensile test, Impact test, Hardness test, Machinability test were performed to obtain the mechanical characteristics of the new found material. The results showed that the less dense Al/RHA/SiC hybrid composites have estimated percent porosity levels as low as < 2.86% porosity.